Phosphorylation of CK1δ: identification of Ser(370) as the major phosphorylation site targeted by PKA in vitro and in vivo - Giamas, Georgios (Portland Press Ltd., 2007)
The involvement of CK1 (casein kinase 1) δ in the regulation of multiple cellular processes implies a tight regulation of its activity on many different levels. At the protein level, reversible phosphorylation plays an important role in modulating the activity of CK1δ. In the present study, we show that PKA (cAMP-dependent protein kinase), Akt (protein kinase B), CLK2 (CDC-like kinase 2) and PKC (protein kinase C) α all phosphorylate CK1δ. PKA was identified as the major cellular CK1δCK (CK1δ C-terminal-targeted protein kinase) for the phosphorylation of CK1δ in vitro and in vivo. This was implied by the following evidence: PKA was detectable in the CK1δCK peak fraction of fractionated MiaPaCa-2 cell extracts, PKA shared nearly identical kinetic properties with those of CK1δCK, and both PKA and CK1δCK phosphorylated CK1δ at Ser(370) in vitro. Furthermore, phosphorylation of CK1δ by PKA decreased substrate phosphorylation of CK1δ in vitro. Mutation of Ser(370) to alanine increased the phosphorylation affinity of CK1δ for β-casein and the GST (gluthatione S-transferase)–p53 1–64 fusion protein in vitro and enhanced the formation of an ectopic dorsal axis during Xenopus laevis development. Anchoring of PKA and CK1δ to centrosomes was mediated by AKAP (A-kinase-anchoring protein) 450. Interestingly, pre-incubation of MiaPaCa-2 cells with the synthetic peptide St-Ht31, which prevents binding between AKAP450 and the regulatory subunit RII of PKA, resulted in a 6-fold increase in the activity of CK1δ. In summary, we conclude that PKA phosphorylates CK1δ, predominantly at Ser(370) in vitro and in vivo, and that site-specific phosphorylation of CK1δ by PKA plays an important role in modulating CK1δ-dependent processes.